Feminismo, estudios culturales y cultura popular - Joanne Hollows (Universitat de Barcelona, 2005)
This paper explores the movement of feminism into academic life in general and the study of popular culture in particular. Assumptioms about the effects of popular culture on women had been a commonsense of second-wave feminism; however, by the mid-1970’s, questions about how gendered identities were culturally produced and reproduced became the topic of much more in-depth feminist research and discussion. This essay examines two main ways in which feminist research into popular culture entered academic life: first, it examines the “images of women” debate, and second, it examines the Cultural Studies tradition and the feminist cultural analysis.